2021
DOI: 10.1136/bmjresp-2021-000907
|View full text |Cite
|
Sign up to set email alerts
|

CPAP delivered outside critical care during the second wave of COVID-19: outcomes from a UK respiratory surge unit

Abstract: BackgroundNHS England recommends non-invasive continuous positive airway pressure (CPAP) as a possible treatment for type 1 respiratory failure associated with COVID-19 pneumonitis, either to avoid intubation or as a ceiling of care. However, data assessing this strategy are sparse, especially for the use of CPAP as a ceiling of care, and particularly when delivered outside of a traditional critical care environment. We describe a cohort of patients from Liverpool, UK, who received CPAP on a dedicated respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Other studies have found intubation may be avoided in 37–80% of patients with COVID-19 undergoing NIPPV [ [42] , [43] , [44] , [45] ]. A retrospective analysis of 88 patients receiving CPAP in the United Kingdom found a 56% survival rate, and a prospective observational study demonstrated 55% of cases successfully avoided intubation using helmet CPAP and were transferred to the general ward [ 46 , 47 ]. The SCCM and NIH guidelines do not include recommendations concerning the use of helmet NIPPV.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found intubation may be avoided in 37–80% of patients with COVID-19 undergoing NIPPV [ [42] , [43] , [44] , [45] ]. A retrospective analysis of 88 patients receiving CPAP in the United Kingdom found a 56% survival rate, and a prospective observational study demonstrated 55% of cases successfully avoided intubation using helmet CPAP and were transferred to the general ward [ 46 , 47 ]. The SCCM and NIH guidelines do not include recommendations concerning the use of helmet NIPPV.…”
Section: Discussionmentioning
confidence: 99%
“…In the second wave, a UK study reported a 56% rate of survival in patients where CPAP was the ceiling of care. Interestingly, the mean time of CPAP use was 9 days ( 55 ). Similar results were reported by Aliberti et al with a mortality of 55% (36/65) in patients with DNI orders using helmet CPAP ( 56 ).…”
Section: Non-invasive Support Modalities Escalating Algorithms and The Role Of Combined Therapiesmentioning
confidence: 99%
“…Its optimal management is still much debated. The efficacy of Non-Invasive Respiratory Support (NRS) as Continuous Positive Airway Pressure (CPAP) and/or Non-Invasive mechanical Ventilation (NIV) in SARS-CoV-2-related hARF is controversial [ 1 3 ], even if several studies support CPAP use [ 4 10 ]. A trial of CPAP seems to significantly reduce mortality and oro-tracheal intubation (OTI) rates compared to conventional oxygen therapy in patients with SARS-CoV-2-related ARDS [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of these alveoli through PEEP would significantly improve hypoxia and may prevent OTI. In addition mortality rates in patients with COVID-19-related ARDS undergoing OTI and invasive mechanical ventilation (IMV) appear extraordinarily high [ 4 , 9 , 11 16 ], up to 97% during first pandemic waves, also due to the associated risk of bacterial superinfection [ 13 ]. More recently Peñuelas et al [ 17 ] reports an overall 180-day survival rates of 59% in patients undergone IMV for COVID-19.…”
Section: Introductionmentioning
confidence: 99%